EFFECTS OF AQUA-AEROBIC EXERCISE ON THE CARDIOVASCULAR FITNESS AND WEIGHT LOSS AMONG OBESE STUDENTS (International Journal of Physiotherapy, 2017)
Background: Evidence revealed that aquatic exercises are safer than land-based exercises and it allows increased movement amplitude and energy expenditure for obese, middle-aged, or elderly people, it is important to ascertain the physiological effects of aqua aerobic exercise on health among the obese students. This study aimed to determine the effects of aqua aerobics exercise on cardiovascular fitness (VO2max and resting HR) and weight loss (weight, BMI, and WHR) among obese students.Methods: Fifty healthy obese college students (22.28±1.83 years) with minimum BMI value of 28 kg.m-², voluntarily took part in this study. They have been divided randomly into an exercising group (n=25 and BMI=33.11±5.32kg.m-2) and control group (n=25 and BMI=33.64±3.12kg.m-2). The exercising group participated in an aqua aerobic exercise at 60-75% of maximum HR for 60 minutes, three times per week for 12 weeks. The changes (by pre and post-test) in weight, WHR, resting HR and VO2max were measured for both groups via In Body Scan 370, Polar heart rate monitor and Bleep test, respectively.Results: There was a significant (p≤0.001) improved in weight loss (-8.78±3.61kg), and the changes of BMI (-3.24±1.1kg.m-2), WHR (-0.056±0.035), resting HR (-1.48±1.004 bmp), and VO2max (4.43±2.51 ml.kg-1. min-1) in the exercising group, compared to the control group. The results indicate that the aqua aerobic exercise is an effective way to enhance cardiovascular fitness and weight loss among obese students.Conclusion: Aqua aerobic exercise as a favorable exercise environment for the obese can be advised such a significant intervention strategy for weight loss and improvement in cardiovascular fitness.